(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Disability was considered to be a curse rather than understanding the biological factors responsible for it and may occur with anyone at any point of time. Since, ancient time disability was considered to be the outcome of sins committed by oneself. It was concluded that through passage of time, people would gradually understand the outcome of disability and its effect on persons with disabilities but instead the opinion has turned to be objects of charity rather than giving importance and mainstreaming them in the society. Researchers, various organizations and Government institutions across the globe have tried to lay down the principles and to realize the society that they are entitled to all fundamental and human rights as other people enjoy in the society under their respective Constitution of their country. If they are given responsibilities, they have the capacity in themselves to prove the mettle and are actually showed to the world. With stringent laws and imposing stern actions on law violators, the conditions of persons with disabilities have been gradually changing but still needs lot of improvement. With the help of this research paper, I have tried to discuss various conceptions in the mindset of people regarding them as objects of charity to giving them importance in the society and thus imparting them respect, dignity and trust them to the core would definitely contribute to the economic conditions of the country.